The Exploration of Performance Evaluation on School Rear-service in China - Lin Shen; Hui Xu (Управленческое консультирование)
The logistic service in China’s schools, especially in college schools, has become more and more socialized, which requires higher quality of the management to meet it. The performance evaluation about school logistic service in China includes six aspects: the effectiveness of the operation system, the quality of the school asset, the ability of the development, the service quality, the social contribution and the level of the management. This paper will introduce the current situation of logistic service management in China’s schools, and then make an analysis of the school logistics performance management, followed by a design of performance evaluation index system of school logistics management, which includes 6 indexes and 42 subindexes, with the purpose of improving the quality of school logistics assets, ensuring sustainable development and perfecting the logistics management and economic efficiency. Finally, the paper will try to propose some suggestions on how to reform the school logistics service performance management in China and learn some useful experience from abroad.